1983
DOI: 10.1002/pi.4980150105
|View full text |Cite
|
Sign up to set email alerts
|

Epoxy systems with improved water resistance, and the non‐fickian behaviour of epoxy systems during water ageing

Abstract: N,N‐Bis (2, 3‐epoxypropyl) aniline and 4,4′‐methylenebis‐[N,N‐bis (2,3‐epoxypropyl) aniline] containing bromo, chloro, trifluoromethyl or polyfluoroalkoxy substituents were synthesised and cured with aromatic diamines in order to investigate the effect of substituted halogen on water absorption. Significant improvements were achieved: thus use of 4,4′‐methylenebis‐[N, N‐bis (2, 3‐epoxypropyl)‐3, 5‐dichloroaniline] and 4,4′‐methylenebis‐[N,N‐bis (2,3‐epoxypropyl)‐3‐(trifluoromethyl) aniline] instead of 4,4′‐met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…This observation can be in part attributed to the relative proximity of the immersion temperature to the glass transition temperature of this wet epoxy system (wet T g = 142°C as determined by DMA). Hence, viscoelastic effects would contribute to an enhanced water transport into the network, in agreement with previous studies in the literature 37, 57, 58. It is worth mentioning at this point that an “initial saturation” value (as indicated by the arrows) was used to fit the experimental water absorption data using Fick's law; therefore, “apparent” diffusion coefficients are calculated and are summarized in Table II.…”
Section: Resultssupporting
confidence: 83%
“…This observation can be in part attributed to the relative proximity of the immersion temperature to the glass transition temperature of this wet epoxy system (wet T g = 142°C as determined by DMA). Hence, viscoelastic effects would contribute to an enhanced water transport into the network, in agreement with previous studies in the literature 37, 57, 58. It is worth mentioning at this point that an “initial saturation” value (as indicated by the arrows) was used to fit the experimental water absorption data using Fick's law; therefore, “apparent” diffusion coefficients are calculated and are summarized in Table II.…”
Section: Resultssupporting
confidence: 83%
“…Barrie et al [5] included the possibility of clustering of water molecules at high moisture levels. It has also been proposed that the equilibrium water concentration is mainly governed by the available free volume [4,6,7], or that water molecules occupy microvoids and other defects [8][9][10]. Previous studies [11][12][13][14][15][16] show that water molecules are linked by strong hydrogen bonds to hydrophilic groups such as hydroxyl and amine groups.…”
Section: Introductionmentioning
confidence: 99%
“…81 Changes in the chemicals composition of the resin alter both the rate at which water is absorbed and the extent of absorption, and this is particularly evident when the epoxy contains chlorine, bromine or fluorine atoms. 8284 The diffusion coefficients are influenced by the functionality of the epoxy and the amine which in turn influences the free volume. The free volume is reflected in the T g and the diffusion coefficients scale roughly with its value; a high T g material will usually have a low diffusion coefficient.…”
Section: Mechanisms Of Ageing In Various Environmentsmentioning
confidence: 99%
“…Comparison of joints produced using processes involving grit-blast and degreasing (GBD), phosphoric-acid anodising (PAA), and PAA followed by the application of an anti-corrosion primer (PAAP) and subjected to cyclic fatigue tests in liquid water and in 55% relative humidity (RH) has been undertaken. 84 It has been found that there is threshold for the adhesive fracture energy, G th , below which crack growth will not occur. For the GBD pre-treated joints, tested in both the liquid water and in 55% RH environments, failure occurs predominantly by the thermodynamic displacement of the adhesive from the metal substrate.…”
Section: Mechanisms Of Ageing In Various Environmentsmentioning
confidence: 99%